2008
DOI: 10.1017/s0265021508003670
|View full text |Cite
|
Sign up to set email alerts
|

Transoesophageal echo-Doppler vs. thermodilution cardiac output measurement during hepatic vascular exclusion in liver transplantation

Abstract: Echo-Doppler cardiac output values are different from those measured by thermodilution cardiac output in these patients. Echo-Doppler cardiac output monitoring seems to detect the output changes, which can occur during acute haemodynamic changes more rapidly than thermodilution cardiac output in the course of liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Other methods for measuring continuous CO have been evaluated during orthotopic liver transplantation. Transesophageal echo Doppler–determined CO values30 are different from those measured by TDCO, but the method seems to detect the changes in CO more rapidly than TDCO. Measurements of CO by transesophageal echocardiography (TOE)31 seem promising.…”
Section: Discussionmentioning
confidence: 84%
“…Other methods for measuring continuous CO have been evaluated during orthotopic liver transplantation. Transesophageal echo Doppler–determined CO values30 are different from those measured by TDCO, but the method seems to detect the changes in CO more rapidly than TDCO. Measurements of CO by transesophageal echocardiography (TOE)31 seem promising.…”
Section: Discussionmentioning
confidence: 84%
“…Indeed, using TEE and transesophageal echo-Doppler techniques, values similar to those obtained by PRAM are reported [7,8]. Unfortunately, however, intracardiac volumes using TEE and SV determined by the echoDoppler-velocimetry method underestimate by 20-30% SV obtained by magnetic resonance imaging, cineventriculography, and TDCO [11][12][13][14][15][16]. With respect to CI/CO determination by means of ICG in the morbidly obese patient during ppn, Aloni et al [9] reported values essentially equivalent to the TDCO studies of Nguyen et al and Artuso et al Review of the literature, however, shows that ICG systematically underestimates TDCO/ TDCI in the morbidly obese and critically ill patient by 15-20% [17,18].…”
mentioning
confidence: 66%
“…The accuracy of ultrasonic imaging is partly operator-dependent and a training period for handling the transesophageal probe and optimizing the Doppler flow signals improves the reliability of the hemodynamic measurements [31]. Other studies reporting greater percentage errors and a wider range in limits of agreements for CO values did not emphasize the need to verify or optimize probe position before each measurement, nor did they mention the rejection rate of unsatisfactory results [32,33].…”
Section: Discussionmentioning
confidence: 99%